Pre-dopa Deep Brain Stimulation: Is Early Deep Brain Stimulation Able to Modify the Natural Course of Parkinson’s Disease? - Porta, Mauro; Servello, Domenico; Zekaj, Edvin; Gonzalez-Escamilla, Gabriel; Groppa, Sergiu (Frontiers in Neuroscience, 2020)
Deep brain stimulation (DBS) is an established therapy for the management of Parkinson’s disease (PD). However, DBS is indicated as the disease progresses and motor complications derived from pharmacological therapy arise. Here, we evaluate the potential of DBS prior to levodopa (L-Dopa) in improving Quality-of-life (QoL), challenging the state-of-the-art for DBS therapy. We present data on clinical manifestation, decision finding during early indication to DBS and trajectories after DBS. We further discuss current paradigms for DBS and hypothesize on possible mechanisms. Six patients, between 50 and 67 years old, presenting at least 5 years of PD symptoms, and without L-Dopa therapy initiation, received subthalamic nucleus (STN) DBS implantation. In the six PD cases, indication for DBS was not driven by motor complications, as supported by current guidelines, but by relevant QoL impairment and patient’s reluctance to initiate L-Dopa treatment. All patients treated with STN-DBS prior to L-Dopa presented improvement in motor and non-motor symptoms and significant QoL improvement. All patients reduced the intake of dopamine agonists and five are currently free from L-Dopa medication, with no reported adverse events. We introduce a multicentre observational study to investigate whether early DBS treatment may affect the natural course of PD. Early application of DBS instead of L-Dopa administration could have a pathophysiological basis and be prompted by a significant incline on QoL through disease progression; however, the clinical value of this proposed paradigm shift should be addressed in clinical trials aimed at modulating the natural course of PD.